Broadening the phenotypic spectrum of POP1‐skeletal dysplasias: identification of POP1 mutations in a mild and severe skeletal dysplasia. Issue 1 (22nd February 2017) - Barraza‐García, J.; Rivera‐Pedroza, C.I.; Hisado‐Oliva, A.; Belinchón‐Martínez, A.; Sentchordi‐Montané, L.; Duncan, E.L.; Clark, G.R.; del Pozo, A.; Ibáñez‐Garikano, K.; Offiah, A.; Prieto‐Matos, P.; Cormier‐Daire, V.; et al.
Abstract : Processing of Precursor 1 (POP1) is a large protein common to the ribonuclease‐mitochondrial RNA processing (RNase‐MRP) and RNase‐P (RMRP) endoribonucleoprotein complexes. Although its precise function is unknown, it appears to participate in the assembly or stability of both complexes. Numerous RMRP mutations have been reported in individuals with cartilage‐hair hypoplasia (CHH) but, to date, only three POP1 mutations have been described in two families with features similar to anauxetic dysplasia (AD). We present two further individuals, one with severe short stature and a relatively mild skeletal dysplasia and another in whom AD was suspected. Biallelic POP1 mutations were identified in both. A missense mutation and a novel single base deletion were detected in proband 1, p.[Pro582Ser]:[Glu870fs*5]. Markedly reduced abundance of RMRP and elevated levels of pre5.8s rRNA was observed. In proband 2, a homozygous novel POP1 mutation was identified, p.[(Asp511Tyr)];[(Asp511Tyr)]. These two individuals show the phenotypic extremes in the clinical presentation of POP1‐dysplasias. Although CHH and other skeletal dysplasias caused by mutations in RMRP or POP1 are commonly cited as ribosomal biogenesis disorders, recent studies question this assumption. We discuss the past and present knowledge about the function of the RMRP complex in skeletal development. Abstract :